Diagnosing familial hypercholesterolaemia in childhood by measuring serum cholesterol. Issue 6076 (18th June 1977) - Leonard, J V; Whitelaw, A G; Wolff, O H; Lloyd, J K; Slack, J
Abstract : The serum cholesterol concentrations of 134 children aged 1-16 years who had at least one first-degree relative with presumed familial hypercholesterolaemia showed a bimodal distribution, and, using the maximum likelihood technique, two overlapping curves could be fitted. The mean value of the affected children (heterozygotes) was 8-9 mmol/l and that of the unaffected 4-9 mmol/l. The two curves intersected at 6-77 mmol/l, and at this point 5% of the unaffected children had values over 6-77 mmol/l and 3-5% of the heterozygotes had values under 6-77 mmol/l. If this cholesterol concentration is used as a cut-off point 4-25% of cases would be misdiagnosed.